Avtorska slikanica Lile Prap - Haramija, Dragica (Revija za elementarno izobraževanje, 2008)
Lilijana Praprotnik - Zupančič, better known under her artistic name Lila Prap, is an important picture book author whose works have received numerous awards for children's literature at home and abroad. This article concentrates on presenting all of Lila Prap's picture books and evaluates her works in their textual as well as visual aspects, which are equivalent components. From a literary point of view her works can be divided into three categories: poetry (four of the picture books are poetry collections entitled Tiny creatures, Animal Lullabies, Why and Daddies), prose (the picture book entitled 1001 Fairy Tales is a fairy tale) and informative literature (Animal Alphabet, International Animal Dictionary). The simplistic poetical approach of Lila Prap is based on word plays and puns which the writer uses to intentionally transgress phonetic, formal and/or syntactic linguistic elements. A simplification which does not slip into banality, an expressive playfulness and nonsense which creates a comical atmosphere, these are the elements of the writer's creativity which testify to the wittiness and quality of her books. The excellence of her picture books can be perceived on a linguistic level as well as a visual artistic level, thus creating a quality artistic picture book intended for children at the prereading and early reading development stage. In its visual aspects the work of Lila Prap is a good example of using innovative painting techniques that exploit and intentionally adapt to their potentials. Lila Prap's visual language is used purposefully and is distinguished by its stylistically recognizable language of signs.
Keywords: Praprotnik-Zupančič, Lilijana, 1955-; ocene in poročila; Slovene literature; slovenska književnost; slovenska mladinska književnost; slovenske pisateljice; slikanice; literarne študije